Homerowe ślady w "Prawdziwej historii" Lukiana z Samosat - Tylak, Aneta (Collectanea Philologica, 2024)
Lucian of Samosata was one of the representatives of the Second Sophistic who referred to Homer’s poems in his work. There are many opinions in the literature that Lucian mocked Homer in order to belittle his authority. Lucian’s work A True Story does not shy away from references to Greece’s first poet, including in the context of humour and parody. The aim of this article is to show how Lucian uses Homer’s epics in A True Story – can we say that the reception Lucian makes in his satire only shows that the Greek poet was fodder for mockery, or can we also see there some signs of respect for Homer.